Real-World Metastatic Renal Cell Carcinoma Treatment Patterns and Clinical Outcomes in The Netherlands - van Laar, S.A.; Gombert-Handoko, K.B.; Groenwold, R.H.H.; van der Hulle, T.; Visser, L.E.; Houtsma, D.; Guchelaar, H.J.; Zwaveling, J. (Frontiers in Pharmacology, 2022)
The number of treatment options for patients with metastatic renal cell carcinoma (mRCC) has significantly grown in the last 15 years. Although randomized controlled trials are fundamental in investigating mRCC treatment efficacy, their external validity can be limited. Therefore, the efficacy of the different treatment options should also be evaluated in clinical practice. We performed a chart review using electronic health records (EHRs) text mining software to study the current treatment patterns and outcomes. MRCC patients from two large hospitals in the Netherlands, starting treatment between January 2015 and May 2020, were included. Data were collected from EHRs using a validated text mining tool. Primary endpoints were progression-free survival (PFS) and overall survival (OS). Statistical analyses were performed using the Kaplan-Meier method. Most frequent first-line treatments were pazopanib (n=70), sunitinib (n=34), nivolumab with ipilimumab (n=28). The overall median PFS (mPFS) for first-line treatment was 15.7 months (95% confidence interval [(95%CI], 8.8–20.7); 16.3 months (95%CI, 9.3– not estimable [NE]) for pazopanib, and 6.9 months (95% CI, 4.4–NE) for sunitinib. The overall median OS (mOS) was 33.4 months (95%CI, 28.1–50.9 months); 39.3 months (95%CI, 29.5–NE) for pazopanib, and 28.1 months (95%CI, 7.0–NE) for sunitinib. For nivolumab with ipilimumab, mPFS and mOS were not reached. Of the patients that finished first- and second-line treatment, 64% and 62% received follow-up treatment. With most patients starting on pazopanib and sunitinib, these real-world treatment outcomes were most likely better than in pivotal trials, which may be due to extensive follow-up treatments.